Carbosilane Dendritic Amphiphiles from Cholesterol or Vitamin E for Micelle Formation - Gabriel Mencia; Sergio Algar; Tania Lozano-Cruz; Mª Ángeles Muñoz-Fernández; Elizabeth R. Gillies; Jesús Cano; Mercedes Valiente; Rafael Gómez (MDPI AG, 2024)
Cationic dendritic amphiphiles were prepared through the linkage of interesting hydrophobic molecules such as cholesterol or vitamin E to the focal point of carbosilane dendrons. These new dendritic systems self-assembled in saline, producing micellar aggregates with hydrodynamic diameters ranging from 6.5 to 9.2 nm, and critical micelle concentrations of approximately 5 and 10 μM for second- and third-generation systems, respectively. The assemblies were able to encapsulate drugs of different charges (anionic, neutral, and cationic). Surprisingly, a 92% encapsulation efficiency for diclofenac was achieved in micelles prepared from second-generation dendrons. Toxicity measurements on peripheral blood mononuclear cells indicated different behavior depending on the generation, corresponding to the micellar regime. In contrast to the third-generation system, the second-generation system was non-toxic up to 20 μM, opening a window for its use in a micellar regimen, thereby operating as a drug delivery system for different biomedical applications.